PENGGUNAAN VIRLENDA DALAM PEMBELAJARAN MENULIS KARYA ILMIAH DI MASA PANDEMI COVID-19 PADA MAHASISWA PGSD - Amelia Widya Hanindita (Universitas Negeri Surabaya, 2021)
The purpose of the study was to describe the implementation, results, constraints, and responses to the use of VIRLENDA in learning to write scientific papers during the Covid-19 pandemic for PGSD students. The research method uses a descriptive quantitative approach. Data analysis techniques in the study used descriptive analysis and content analysis. The results showed that the implementation of the use of VIRLENDA in learning to write scientific papers during the Covid-19 pandemic for PGSD students took place in a very orderly manner. The results of using VIRLENDA in learning to write scientific papers during the Covid-19 pandemic, PGSD students obtained varied scores. The obstacles found during the use of VIRLENDA in learning to write scientific papers during the Covid-19 pandemic for PGSD students were due to the internet network, the emergence of boredom, difficulty in concentrating, and lack of time management. PGSD students gave a good response to the use of VIRLENDA in learning to write scientific papers during the Covid-19 pandemic.